Effect of Foliar-applied Plant Growth Regulators on Coriander (Coriandrum sativum L.) to Regulate Growth and Yield Attributes - Shreyansha Dubey; Reena Nair; Surabhi Jain; Ankita Sharma; Harshita Thakur; Monika Koushale; Shubham Ahirwar (Archives of Current Research International, 2024)
This investigation was conducted to obtain the effect of plant growth regulator on growth, yield and quality. The experiment utilized a randomized block design with three replications and nine treatments, including a control. The four different plant growth regulators (PGRs) used were Benzyl adenine (BA, 10 and 20 ppm), Brassinosteroid (BR, 0.5 and 1.0 ppm), Jasmonic acid (JA, 50 and 100 ppm) and Salicylic acid (SA, 50 and 100 ppm), applied as foliar sprays at 30 and 60 days after sowing (DAS). The experiment was conducted during the Rabi season of 2023-24 at the Vegetable Research Centre, Maharajpur, Department of Horticulture, College of Agriculture, Jawaharlal Nehru Krishi Vishwa Vidyalaya, Jabalpur, Madhya Pradesh. The investigation revealed that BR at 0.5 ppm resulted in the maximum plant height (103.67 cm). The highest number of primary (15.53) and secondary (26.50) branches at harvest was achieved with JA at 50 ppm. Phenological observations indicated that JA at 50 ppm led to the earliest 50% flowering at 36.67 days. For yield attributes, the highest number of umbels per plant (42.13) and umbellets per umbel (6.31) were found with JA at 50 ppm. BA at 20 ppm showed the maximum number of seeds per umbel (36.40), test weight (10.84 g), harvest index (9.92), and seed yield (13.65 q ha-1). Economically, BA at 20 ppm provided the highest net return (Rs. 170735.81), gross return (Rs. 232117.39), and benefit-cost ratio (2.78). Therefore, it can be concluded that foliar sprays of BR, JA, and BA are effective on improving phenological traits, yield attributes, and economic returns in coriander cultivation.